Research methods and statistics : a critical thinking approach - Jackson, Sherri L. , 1962- (Wadsworth Cengage Learning, 2012)
RESEARCH METHODS AND STATISTICS: A CRITICAL THINKING APPROACH, 4e, successfully illustrates the integration between statistics and research methods by demonstrating the ways to use statistics in analyzing data collected during research. Jackson's combined text adopts an inviting narrative style that draws you into the material, helping you overcome the initial apprehension you may feel at having to learn both subject areas at once. She incorporates a student-friendly critical-thinking approach and presents examples and exercises to which you can relate. Jackson focuses on the logic of the process and the methodology aspect of research